Elderly Took Preventive Role in Facing Flood Threat in Mountain Slope Area in Jember, East Java - Citra Anggun Kinanthi; Adistha Eka Noveyani; Arsyzilma Hakiim (Jurnal Pengabdian West Science, 2023)
Tempurejo Subdistrict is a cantilever for Meru Betiri National Park in the southern part of the Jember Regency. In every rainy season, several villages in this sub-district are flooded. Hence flood disaster preparedness education becomes very necessary. Knowledge and understanding of disaster preparedness must be known to anticipate disaster situations quickly and accurately. The purpose of this activity is to provide education to the community regarding before, during, and after disaster management. In addition, to maintain the sustainability of the community, a sub-district disaster preparedness team was formed and continuously assisted. The activity was held in October 2021 with the target of Karang Wreda Abiyoso members. Counseling materials were related to flooding disaster preparedness and the risk disease of post-flood through videos and disaster response pocketbooks. As a result, there was an increase in the post-test than the pre-test, so this counseling effectively increased the participants' knowledge.Furthermore, disaster response training was carried out, and one of the training courses was preparing a disaster preparedness bag. As a result, 9 out of 10 participants could simulate the preparation of a disaster preparedness bag within the allotted time. Furthermore, continuous assistance was carried out through the WhatsApp Group. This team is expected to be able to disseminate disaster preparedness knowledge to residents and increase understanding regarding appropriate disaster preparedness in their area.